An assessment of implementation science research capacity in Uganda - Aggrey S. Semeere; Fred C. Semitala; Olivia Lunkuse; Anne Katahoire; Nelson K. Sewankambo; Moses R. Kamya (BMC, 2021)
Abstract Background In Uganda and other resource-poor countries, relevant research findings face a tortuous path to translation into policy and routine practice. Implementation science (ImSc) research could facilitate faster translation. Presently it is unclear what ImSc research capacity and possible training needs exist among Ugandan researchers. To assess both components, we interviewed potential trainees in Kampala, Uganda. Methods We used a cross-sectional design to survey potential ImSc trainees who had some research training and involvement in generating or utilizing research. Using a questionnaire, we documented eligibility for ImSc training, knowledge and interest in training, existing self-assessed confidence in initiating clinical research (SCICR) and self-assessed confidence in initiating ImSc research (SCIIR), availability for training and preferred modes of training. We developed scores from the Likert scales and used descriptive statistics, logistic regression and ordinal logistic regression to evaluate predictors of SCIIR. Results Between November 2016 and April 2017, we interviewed 190 participants; 60% were men, with a median age of 37 years. Among participants, 33% comprised faculty, 37% were graduate students and 30% were project staff. The majority of respondents knew about ImSc (73%) and were research-trained (80%). Only 9% reported any ImSc-related training. Previous ImSc training was associated with higher odds of a SCIIR score ≥ 75th percentile. Previous ImSc training compared to not having any training was associated with higher odds of reporting abilities in behaviour change theory integration (OR: 3.3, 95% CI: 1.3-8.5, p = 0.01) and framework use in intervention design and implementation (OR: 2.9, 95% CI: 1.1-7.4, p = 0.03), accounting for age, sex and current employment. In addition, 53% of participants preferred in-person (face-to-face) short ImSc courses compared to a year-long training, while 33% preferred online courses. Participants reported median availability of 6 hours per week (IQR: 4, 10) for training. Conclusion Most participants had some understanding of ImSc research, had research training and were interested in ImSc training. Those with previous ImSc training had better skills and SCIIR, compared to those without previous training. A hybrid approach with modular face-to-face training and online sessions would suit the preferences of most potential trainees.